1998
DOI: 10.1097/00000539-199812000-00010
|View full text |Cite
|
Sign up to set email alerts
|

End-Tidal Sevoflurane Concentration for Tracheal Extubation and Skin Incision in Children

Abstract: Because tracheal extubation of anesthetized patients may be advantageous in certain clinical situations, we performed this study. The ratio minimum alveolar anesthetic concentrations for skin incision and for tracheal extubation for sevoflurane was 0.8 in children within the same age range and mean age. No patient in the current study had laryngospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Loss of eyelash reflex test became negative with 5% sevoflurane in 132.6 ± 9.32 sec in our study while it was 147 seconds in another study in children without opioids 11 . This was due to the difference in the flow rate of oxygen gas, age, and opioids are given.…”
Section: Methodcontrasting
confidence: 40%
“…Loss of eyelash reflex test became negative with 5% sevoflurane in 132.6 ± 9.32 sec in our study while it was 147 seconds in another study in children without opioids 11 . This was due to the difference in the flow rate of oxygen gas, age, and opioids are given.…”
Section: Methodcontrasting
confidence: 40%
“…Both Dexmedetomidine and Clonidine mainly are α 2 adrenergic receptor agonists with weak action on α 1 receptors. But, the ratio of selectivity to α 2 receptors for Dexmedetomidine is eight to ten times greater than that of clonidine [ 14 ] leading to better sedative effect and less side effect of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Inomata et al reported that the MAC EX value of sevoflurane in children was 1.64% with the administration of N 2 O but without systematic analgesics [ 14 ]. In this present study, we found the MAC EX value of sevoflurane for smooth extubation to be 1.40% in Group D 0 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that adequate ventilation was maintained and smooth extubation was safely performed at 1.3 MAC of sevoflurane with 2 lgAEkg )1 fentanyl. Importantly, Inomata et al (12) found that the 95% effective dose of sevoflurane for a smooth extubation was 1.87% in children aged 2-8 years; however, the authors could not exclude the effects of nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Inomata et al. (12) found that the 95% effective dose of sevoflurane for a smooth extubation was 1.87% in children aged 2–8 years; however, the authors could not exclude the effects of nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%